Effect of fertilization on yields and fodder value of winter pea cv. Maksimirski ozimi in wheat cv. Sana mixture - Darko Uher; Sulejman Redžepović; Zlatko Svečnjak; Mihaela Blažinkov; Dražen Kaučić (Mljekarstvo)
Two year field trials (1999-2001) were carried out to determine the effect of seed winter pea inoculation and nitrogen top-dressing effect on nodule dry weight of pea root and also on the dry matter yield and fodder value of winter pea cv. Maksimirski ozimi and wheat cv. Sana mixture. Just before sowing the inoculation of pea seeds was performed by the indigenous variety of Rhizobium leguminosarum bv. viciae which is part of the microbial collection of the Department of Microbiology at the Faculty of Agriculture University of Zagreb. The highest total nodule dry weight on pea root was determined on the inoculated variant 2 (0.710 g/variant). Total dry matter yields were ranging from 8.64 t ha-1 (control) up to 10.98 t ha-1 (inoculation). Yields crude proteins pea in 2001 were ranging from 942 kg ha-1 (control) up to 1510 kg ha-1 (inoculation) and for wheat, those values were from 450 kg ha-1 (control) up to 813 kg ha-1 (nitrogen top-dressing). Total crude proteins mixture yields were from 1392 kg ha-1 (control) up to 2140 kg ha-1 (inoculation).